2015
DOI: 10.1109/tdei.2015.7116371
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic potential distributions of surface discharge in silicone gel

Abstract: Silicone gel is widely used to encapsulate power electronic circuits. It is known that the weakness of this insulation system is the surface discharges between gel and substrate. These discharges give rise to the growth of cavities in gel, which may lead to eventual failure of the insulation. Despite the fact, surface discharges in gel has not yet been studied enough. In order to clarify the nature of streamers in the cavity and relation between streamer propagation and charge accumulation at the interface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…This value, which is close to the critical field in air [17], can lead to surface discharges (creeping with tangential field). Such discharges damage the insulation, distort the potential distribution, and can lead to a flashover [19], [26], [27]. The triple points, i.e.…”
Section: Magnetic/electric Field Analysismentioning
confidence: 99%
“…This value, which is close to the critical field in air [17], can lead to surface discharges (creeping with tangential field). Such discharges damage the insulation, distort the potential distribution, and can lead to a flashover [19], [26], [27]. The triple points, i.e.…”
Section: Magnetic/electric Field Analysismentioning
confidence: 99%
“…In [14,15], the tests performed followed a classical procedure employed in liquids, with the aim to evaluate the streamer inception (streamer is a term commonly employed for the propagating breakdown structure in liquids) and to compare the behavior observed in the gels with that of silicone oil. In [16,17], the experiments focused on lower AC voltages, highlighting the formation and growth of string of bubbles having the shape akin to an electrical tree in a solid insulator (therefore, referred to as electrical trees, indifferently from the case of solid dielectrics). The tree growth and structure where compared with that of the elastomer by means of their fractal dimension.…”
Section: Introductionmentioning
confidence: 99%
“…All the studies concluded that, regardless of the self-healing behavior of silicone gels, a continuous voltage application leads to the formation of discharge-supporting electrical tree structures [13,16,17], the skeleton of which is permanent [17] (i.e. the material is irreversibly damaged).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the former paper, (1) we have proposed an analyzing procedure for discharges in gel based on motion observation of cavities induced by discharges, and applied to some characteristic motions of the cavity [7], and (2) measured the dynamic potential distributions of surface discharges in silicone gel on glass substrates [8]. The aim of this paper is to confirm validity of the assumption we have made, to investigate discharges on ceramic substrates which are generally used for power modules, and to summarize the features of surface discharge in gel under AC voltage.…”
Section: Introductionmentioning
confidence: 99%